2017
DOI: 10.18203/2349-3933.ijam20171513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neurocognitive deficit among euthymic bipolar I disorder patients, their first-degree relatives and healthy controls

Abstract: Background: Bipolar patients often suffer from debilitating cognitive impairment in different stages of the disease (manic, depressive or euthymic states). We assessed and compared the frequency of neurocognitive deficit among individual with bipolar I disorder but currently in euthymic state, their first-degree blood relatives and healthy controls. In addition, we also probed further into the type of neurocognitive deficit that can be seen among them and observed the influence of sociodemographic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These findings are in concordance with literature that states that there is persistent cognitive impairment in the domains of attention, memory, and executive functions in BPAD patients in the euthymic state. 20 Executive functions, memory, and tasks involving mental flexibility and psychomotor speed are specifically affected in patients with BPAD, 11 which is in concurrence with our finding that speed of processing and problem-solving are two domains that have yielded medium effect size in performance amongst patients and FDR.…”
Section: Neurocognitionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are in concordance with literature that states that there is persistent cognitive impairment in the domains of attention, memory, and executive functions in BPAD patients in the euthymic state. 20 Executive functions, memory, and tasks involving mental flexibility and psychomotor speed are specifically affected in patients with BPAD, 11 which is in concurrence with our finding that speed of processing and problem-solving are two domains that have yielded medium effect size in performance amongst patients and FDR.…”
Section: Neurocognitionsupporting
confidence: 84%
“…According to National Mental Health Sur-sessing the neurocognitive functioning in stable patients with BPAD reported that compared to controls, the patients performed poorly overall in frontal functions, with lower scores in Mini Mental State Examination and Trail Making A and B, indicative of deficits in general cognitive abilities. 20 Currently, deficits with clinical significance have been identified only in symptomatic patients, but these impairments persist even in the remission phase, leading to poor prognosis. [9][10][11] It has been observed that cognitive abilities such as executive functioning and attention are compromised in first-degree relatives (FDR) of patients with BPAD when compared to healthy controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although FAB [64].Regarding psychiatric illnesses, only EXIT-25 and FAB test can evaluate the cognitive tasks and be associated with specific areas of the frontal lobes (that is, able to measure, i.e., conceptualization with the dorsolateral areas, word generation with the medial areas, and inhibitory control with the orbital or medial areas, just as the FAB test was able to exhibit a degree of sensitivity to focal lesions near the anterior insula in the middle right lower frontal gyrus, and in the lower right frontal gyrus), [65]; [66], but, it will be discussed forward.…”
Section: The Frontal Assessment Battery (Fab)mentioning
confidence: 99%
“…Although FAB [64]. Regarding psychiatric illnesses, the FAB test can evaluate the cognitive tasks and be associated with specific areas of the frontal lobes (that is, able to measure, i.e., conceptualization with the dorsolateral areas, word generation with the medial areas, and inhibitory control with the orbital or medial areas.…”
Section: The Frontal Assessment Battery (Fab)mentioning
confidence: 99%